Recent Topics in Electromagnetic Compatibility - Kishk, Ahmed (IntechOpen, 2022)
Recent Topics in Electromagnetic Compatability discusses several topics in electromagnetic compatibility (EMC) and electromagnetic interference (EMI), including measurements, shielding, emission, interference, biomedical devices, and numerical modeling. Over five sections, chapters address the electromagnetic spectrum of corona discharge, life cycle assessment of flexible electromagnetic shields, EMC requirements for implantable medical devices, analysis and design of absorbers for EMC applications, artificial surfaces, and media for EMC and EMI shielding, and much more.